Moral, Educational and Social Values in The Novel Dia Adalah Kakakku by Tere Liye - Yessi Oktarina; Ratu Wardarita; Sri Wahyu Indrawati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The novel Dia Adalah Kakakku contains a story about the sacrifice of the main character, describing the person as a human being who prioritizes family, full of educational and social-moral values. This research aims to find out the values contained in the novel Dia Adalah Kakakku. The method used in this research is descriptive qualitative methods with data collection techniques using note-taking and documentation techniques, with data validity techniques using Triangulation. Research on this novel was carried out by analyzing the moral, educational, and social values in the novel Dia Adalah Kakakku. So the results obtained are that there are values contained in the novel, namely moral values, educational values, and social values.